A label-free PEC aptasensor platform based on g-C3N4/BiVO4 heterojunction for tetracycline detection in food analysis. (15th February 2023) - Zhao, Zhengzheng; Wu, Zhifang; Lin, Xueling; Han, Fangjie; Liang, Zhishan; Huang, Likun; Dai, Mengjiao; Han, Dongxue; Han, Lipeng; Niu, Li
Highlights: A low-cost PEC aptasensor based on g-C3 N4 /BiVO4 was designed for TC detection. The platform has a wide linear range, low LOD, high specificity, good stability. This method successfully achieves the immediate detection of TC in food samples. The platform possesses a broad analysis application prospect. Abstract: A simple low-cost label-free photoelectrochemical (PEC) biosensing platform based on red blood cell shaped BiVO4 modified g-C3 N4 was designed for tetracycline detection under room temperature. The prepared g-C3 N4 /BiVO4 heterojunction not only demonstrated a high surface area, excellent physicochemical stability and favorable PEC activity, but also can be employed as nanostructure support for aptamers to construct a visible-light-driven PEC aptasensor due to rich π-π accumulation sites. More importantly, the proposed PEC aptasensor showed a favorable linear toward tetracycline in the range from 5 × 10 -9 to 2 × 10 -7 M with a detection limit of 1.6 nM, which well covered the Food Standards Testing requirements. Practical food sample analysis further revealed the accuracy and feasibility of the g-C3 N4 /BiVO4 heterostructure based PEC platform. It is expected that such a label-free and cost-effective PEC strategy should act as a promising candidate for tetracycline determination in food quality control and supervision.